Creating Integrated Business and Environmental Value within the Context of China's Circular Economy and Ecological Modernization - Park,J; Sarkis,J; Wu,Zhaohui (Journal of Cleaner Production, 2010)
This paper investigates the challenges and opportunities of how firms and organizations can and will be able to strike a better balance between economic growth and environmental stewardship in the context of China’s emerging ‘circular economy’ policy paradigm and based on ecological modernization theoretic approaches. Based on three company case studies in the information technology and electronic industries in China, we identify and demonstrate how a blended business and environmental value can be created from adopting a sustainable supply chain management approach. The adoption of a sustainable supply chain management approach is rapidly becoming a key business challenge and opportunity in China and other large emerging economies around the world, where our greatest environmental management challenges currently reside and will continue to exist for many years to come. The value creation framework proposed in research focuses on evaluating three case study companies who appear in various stages of an electronic industry supply chain. Value creation within a supply chain can provide the impetus for organizations to adopt circular economy, sustainable supply chain practices, for competitive reasons. In addition, we describe how a value proposition can be evaluated at two levels of analysis, a more specific micro-level and a more general meso-level of analysis. The four major business value dimensions include cost reduction, revenue generation, resiliency, and legitimacy and image. The initial findings are that a variety of opportunities exist for electronic firms in emerging and developing countries, while results from this study provide an important scholarly foundation to develop and refine sustainable supply chain management practices in emerging and developing economies.
Keywords: Supply Chain